PENGGUNAAN TEKS NARASI CERITA RAKYAT UNTUK MENINGKATKAN LITERASI MEMBACA SISWA KELAS III - Nurul Erisa; Nayla Salsabila; Munawarah; Tiara; Khoirunisa Eka Ramadhani; Maimunah; Ahmad Suriansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was motivated by the low reading literacy skills of elementary school students, caused by the limited use of engaging and contextual learning strategies. Third-grade students at SDN Sungai Miai 4 still face difficulties in understanding long reading texts such as folktales, which they often find boring and hard to comprehend. Therefore, this study aims to examine the implementation of using narrative folktale texts to improve the reading literacy skills of third-grade students at SDN Sungai Miai 4. The research employed a simple experimental (quasi-experimental) approach with a descriptive quantitative method. Data were collected through individual reading literacy tests, observations of learning activities, and documentation of the learning process. The results showed that the use of the folktale Timun Mas successfully enhanced students’ literacy skills in reading, writing, listening, and speaking. Students became more active, enthusiastic, and capable of explaining the content of the text in their own words. The learning process also encouraged critical thinking and helped students connect the moral values of the story to their daily lives. Thus, the use of narrative folktale texts proved effective as a learning strategy to improve reading literacy skills while fostering positive character development among elementary school students.